Kidney and Liver Disorders Due to Microplastic Exposure: Chronic in Vivo Study in Male White Rats - Hidayat Ramli Inaku, Awaluddin; Hadiyanto, Hadiyanto; Rya Abdurachim, Henna; Bariroh, Tahyatul; Matin, Hashfi Hawali Abdul (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2024)
The increasing use of plastics has caused severe environmental pollution, especially by microplastics with plastic particles of 5 mm or less in diameter. These particles are formed by environmental factors such as weathering and ultraviolet irradiation, thus making environmental pollution worse. This environmental pollution increases human exposure to microplastics through the food chain. Many studies have now reported the adverse effects of exposure to microplastics in food and aquatic organisms. However, relatively few studies have used white rats. the entry of microplastics into white rats can affect two important organs, namely the liver and kidneys, in this study we conducted an in-vivo experimental test of male white rats by giving acute and chronic exposure to pure microplastic PE (polyethylene) for 28 days respectively. repeated with an adjusted dose. Toxicological effects were comprehensively evaluated in white rats by looking at clinical signs, body weight, and kidney and liver activity through examination of blood parameters creatinine, SGOT, SGPT, and further kidney and liver abnormalities were analyzed through histopathological tests. Based on the results of the experiments conducted, it was found that PE-type microplastics had a significant impact on changes in body weight, increased functional activity of the kidneys and livers of white rats, and chronic histopathological abnormalities in male white rats, so it is hoped that this study can clarify that PE type microplastics greatly affect organs for those who consume it in the long term.